KAJIAN BAHAN TAMBAH ATERNATIF SERAT ECENG GONDOK TERHADAP CAMPURAN LATASIR SAND SHEET KELAS A SPESIFIKASI SEKSI-6 2010 BINA MARGA - Dwi Kartikasari; Ilham sudarso (U Karst, 2017)
The test was carried out by adding water hyacinth fibers in the sand sheet class A latasir mixture. And with the addition of water hyacinth fiber variations of 0.6%, 0.9%, 1.2% taken from asphalt content. The final result of this research was Marshall evaluation which was obtained for the effect of the addition of water hyacinth cellulose fiber in this study showed an increase in Marshall stability value of 27.29% with a mixture of 1.2% water hyacinth, plastic fatigue (Flow) decreased by -23 , 89% with a mixture of 0.9% water hyacinth, cavity filled in the mixture (Void in the Mix) increased by 18.65% with a mixture of 1.2% water hyacinth, cavity filled with asphalt (Void Filled With Asphalt) decreased by -8.74% with a mixture of 1.2% water hyacinth, cavity in aggregate (Void In Mineral Aggregate) increased by 7.80% with a mixture of 1.2% water hyacinth, and Marshall Quotient increased by 71.78% with a mixture of 0.9% water hyacinth. These results indicate that water hyacinth fiber can be used as an ingredient to add a mixture of latasir sand sheet class A specifications of clan development.